Limiting equations for the class number of the ideals of an imaginary quadratic field - Saparnijazov, O. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:О. Сапарниязов. Асимптотические равенства для числа классов идеалов мнимого квадратического поляO. Saparnijazovas. Menamojo kvadratinio skaičių kūno idealų klasių skaičiaus asimptotinės išraiškos